Developing android-based literature theory learning media using the MIT App inventor application - Kurniawan, Rio; Hamzah, Syukri; Hiasa, Fina (UNIB Press, 2024)
This study aims to develop an Android-based literary theory learning media using the inventor application in the independent learning era - independent campus. This study used the Research and Development (R & D) that refers to the model of the research and development of 4D (four-D), which is definition, design, development, and dissemination. The Android-based learning media developed was tested on students in the odd semester taking the course of Theory of Literature at the Department of Indonesian Education, Faculty of Teacher Training and Education, University of Bengkulu. Based on the results obtained from the questionnaires that were distributed in this study, which were from the results of material validation, data related to the learning media used in this study were declared suitable for use without revision. In terms of media appearance and display (text on the media, color combination on the media, images on the media, navigation board layout), the result in general was